The Ways We Stretch Toward One Another : Thoughts on Anthropology through the Work of Pamela Reynolds - Meyers, Todd (African intellectuals., 2018)
The Ways We Stretch Toward One Another is a collection of essays on the work of Pamela Reynolds. The essays take cues from Reynolds' decades-long contributions to the field of anthropology in different ways. The authors weave Reynolds' groundbreaking scholarship on the anthropology of childhood--of labour, of family, of resistance, justice, war and suffering--through the terms of their own work, in places and contexts that may at first appear quite distant from the villages of Zimbabwe and townships of South Africa that feature in Reynolds' ethnographies. The Ways We Stretch Toward One Another is about anthropologists stretching in thought and practice toward one another, between generations, toward the people encountered in the field, through worlds entered and departed, and how, in turn, these worlds lean into our own. At the core of each essay is a question about how we learn, how we pass lessons on, how we assume the mantle of anthropology for understanding the contemporary world--something that often requires folding intellectual friendships into the equipment of our practice. The Ways We Stretch Toward One Another demonstrates how a master anthropologist has come to shape the priorities of others, in terms that are both creative and aware.